Effect of multiple-particle size reinforced silicon carbide(SICP) on properties of aluminium matrix composite - Adebisi, Adetayo A.; Maleque, Md. Abdul (2010)
Silicon carbide (SiC) reinforced aluminum metal matrix composite (AMC) exhibits promising properties enhancement in the field of metal matrix composite. Improved properties of reinforced SiCp-AMC can be determined by varying the nature of reinforcement and their volume fraction. AMCs with multiple-particle size (MPS) of SiC were prepared using 20 wt% SiC and developed using stir-casting process on a special oil-tempered sand mould. In this paper, the effect of varying the particle size of SiC for AMC development and application is investigated. The result shows that aluminium matrix composite with multiple-particle size SiC exhibit better properties including wear resistance than single or double particle size SiC reinforcement as a result of proper shielding effect of base metal and the fine particles by the coarse particles. This study could be use to optimise the wear rate of structural applications developed with multiple-particle size aluminium matrix composite.